Acceptability and Feasibility of an Isometric Resistance Exercise Program for Abdominal Cancer Surgery: An Embedded Qualitative Study. (6th October 2020) - Hashem, Ferhana; Stephensen, David; Bates, Amanda; Pellatt-Higgins, Tracy; Hobbs, Ralph (Nobby) Peter; Hopkins, Malcolm; Woodward, Hazel; Stavropoulou, Charitini; Swaine, Ian L.; Ali, Haythem
Although it is recognized in the early stages of cancer recovery that changes in lifestyle including increases in physical activity improves physical function, there are no clear findings whether low versus moderate intensity activity or home or gym exercise offer optimal benefit. Isometric-resistance exercises can be carried out with very little equipment and space and can be performed while patients are bed-bound in hospital or at home. This embedded qualitative study, based in an English hospital trust providing specialist cancer care, was undertaken as a component of a feasibility trial to evaluate the acceptability and feasibility of an isometric-resistance exercise program and explore the suitability of functional assessments by drawing from the experiences of abdominal cancer patients following surgery. Telephone interviews were undertaken with 7 participants in the intervention group, and 8 interviews with the usual care group (n = 15). The gender composition consisted of 11 females and 4 males. Participants' ages ranged from 27 to 84 (M = 60.07, SD = 15.40). Interviews were conducted between August 2017 and May 2018, with audio files digitally recorded and data coded using thematic framework analysis. Our results show that blinding to intervention or usual care was a challenge, participants felt the intervention was safe and suitable aided by the assistance of a research nurse, yet, found the self-completion questionnaire tools hard to complete. Our study provides an insight of trial processes, participants' adherence and completion of exercise interventions, and informs the design and conduct of larger RCTs based on the experiences of abdominal cancer surgery patients.